تقييم مدى قيام مكتب التدقيق الشرعي الخارجي بمسؤوليته تجاه المصارف الإسلامية في مملكة البحرين: Assessing the External Sharia Audit Office’s Fulfillment of its Responsibilities towards Islamic Banks in the Kingdom of Bahrain - All Mahmud, AbduNasir Umar; Habeebullah Zakariyah (International Journal of Al-Turath In Islamic Wealth and Finance, 2023)
الملخص يَلزم المصارف الإسلامية لممارسة الصيرفة المالية الإسلامية في مملكة البحرين تعيين هيئة للرقابة الشرعية لا يقل أعضاؤها عن ثلاثة من أصحاب الاختصاص في الشريعة والفقه الإسلامي والمعاملات المصرفية الإسلامية وإدارة للتدقيق الشرعي الداخلي وإدارة للتنسيق والتنفيذ الشرعي تابعتان للهيئة الشرعية، كما ويُلزم مصرف البحرين المركزي المصارف الإسلامية تعيين مدقق خارجي وإدارة للتدقيق الداخلي وهو ما يشكل تحدي وعبئ مالي ورقابي على المصارف الإسلامية، وفي عام 2019 أصدر مصرف البحرين المركزي قراراً يُلزم جميع المصارف الإسلامية تعيين مكتب للتدقيق الشرعي الخارجي لإبداء رأياً محايداً عن امتثال المصارف الإسلامية بالمعايير الشرعية والحوكمة الشرعية ومبادئ وأحكام الشريعة الإسلامية وهو ما شكل تحدياً جديداً لمكاتب التدقيق الخارجية التي قد تواجه كثير من التحديات في أداء مسؤوليتها بشكل فعال وفعَّال في إيجاد أداة للقياس في ممارسة وظيفة التدقيق الشرعي الخارجي للوصول إلى تفسيرات مقبولة لدى المصارف الإسلامية حول الامتثال لمبادئ وأحكام الشريعة الإسلامية. يهدف الباحث من خلال البحث إلى استكشاف دور ومسؤوليات مكتب التدقيق الشرعي الخارجي في مدى قيامه بالدور المهم تجاه المسؤولية الأساسية التي من أجلها تم إلزام جميع المصارف الإسلامية في مملكة البحرين في سنة 2019 والتعرف على أهمية عمله كجهة خارجية محايدة في الحفاظ على نزاهة وامتثال المصارف الإسلامية لمبادئ وأحكام الشريعة لكسب ثقة العملاء وأصحاب المصلحة والجهات الرقابية والإشرافية. اعتمد الباحث في البحث على المنهج النوعي وتحليل ومناقشة المقابلات التي استخدمت كأداة من أدوات البحث المتعلقة بمدى قيام مكتب التدقيق الشرعي الخارجي بمسؤولياته تجاه المصارف الإسلامية توصل الباحث إلى أهم الاستنتاجات والتوصيات والتي من أهمها؛ أنه يجب على مكاتب التدقيق الشرعي الخارجي ممارسة مسؤولياتها حول التأكيد على التزام المصارف الإسلامية بفحص التزمها بالمعايير الشرعية وفتاوى وقرارات الهيئة الشرعية ، وتطبيق الحوكمة الشرعية والقوانين واللوائح الصادرة من الجهات الرقابية ، من خلال معيار الضبط رقم (6) المعتمد من هيئة المحاسبة والمراجعة للمؤسسات المالية الإسلامية. Abstract: To practice Islamic financial banking in the Kingdom of Bahrain, Islamic banks are required to appoint a Sharia Supervisory Board consisting of not less than three specialists in Shariah, Islamic jurisprudence, Islamic banking transactions, as well as a department for internal Sharia audit, and another for Sharia coordination and implementation affiliated to the Sharia board. The Central Bank of Bahrain requires Islamic banks to appoint an external auditor and to have an internal audit department, which is a financial and regulatory challenge to Islamic banks. In 2019, the Central Bank of Bahrain issued a resolution requiring all Islamic banks to appoint an external Sharia audit office to provide an objective opinion on Islamic banks’ compliance with Sharia standards and governance, as well as the principles and provisions of Islamic Shariah. External audit offices may face many challenges in playing their roles effectively and efficiently and establishing a tool to evaluate the practice of the external Shariah audit to give interpretations acceptable to Islamic banks regarding compliance with the principles and provisions of Islamic Shariah. The researcher aims to explore the roles and responsibilities of the external Sharia audit offices towards Islamic banks in the Kingdom of Bahrain and the extent to which they comply with the resolution issued by the Central Bank of Bahrain in 2019 and to identify the importance of the work of audit offices as neutral external bodies in maintaining the integrity of Islamic banks and complying with the principles and provisions of Shariah to gain the trust of customers, stakeholders, and regulatory and supervisory authorities. The researcher has adopted the qualitative approach, as well as analyzing and discussing the interviews that were used as one of the research tools related to the extent to which the external Sharia audit offices assume their responsibilities towards Islamic banks. The researcher’s most important findings and recommendations include that the external Shariah audit offices must assume their responsibilities regarding assuring that Islamic banks comply with Sharia standards, fatwas, and resolutions of the Sharia Board, as well as Sharia governance, laws, and regulations issued by the supervisory authorities, by auditing standard No. (6) approved by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI).